2021
DOI: 10.3389/fcimb.2021.743616
|View full text |Cite
|
Sign up to set email alerts
|

Host Blood Gene Signatures Can Detect the Progression to Severe and Cerebral Malaria

Abstract: Malaria is a major international public health problem that affects millions of patients worldwide especially in sub-Saharan Africa. Although many tests have been developed to diagnose malaria infections, we still lack reliable diagnostic biomarkers for the identification of disease severity, especially in endemic areas where the diagnosis of cerebral malaria is very difficult and requires the exclusion of all other possible causes. Previous host and pathogen transcriptomic studies have not yielded homogenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Many whole-blood transcriptomic malaria studies have also identified differences in gene expression between UM and the various SM syndromes [ 3 , 4 ], as well as between malaria and other acute febrile illnesses [ 20 , 21 ]. Such differences in gene expression may form the basis for future diagnostic tests that distinguish between UM and SM, and between malaria and other causes of febrile illness.…”
Section: Diagnosticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many whole-blood transcriptomic malaria studies have also identified differences in gene expression between UM and the various SM syndromes [ 3 , 4 ], as well as between malaria and other acute febrile illnesses [ 20 , 21 ]. Such differences in gene expression may form the basis for future diagnostic tests that distinguish between UM and SM, and between malaria and other causes of febrile illness.…”
Section: Diagnosticsmentioning
confidence: 99%
“…Many studies using transcriptomics to classify subjects based on current disease severity have claimed prognostic value and mention how genes are associated with disease ‘progression’ but have not formally evaluated prediction of future outcomes [ 3 , 34 , 35 ]. This has led to some confusion in the literature about the prognostic potential of transcriptomics, although classifying subjects as severe or non-severe does have intrinsic prognostic value because SM, by definition, carries an increased risk of death or disability [ 34 , 36 ].…”
Section: Prognosticsmentioning
confidence: 99%
See 1 more Smart Citation